Drug use evaluation of cotrimoxazole prophylaxis in people living with human immunodeficiency virus/acquired immune deficiency syndrome at Jimma University Specialized Hospital, Jimma, South West of Ethiopia, 2013 - Defersha, Amsalu Degu; Gelaw, Belayneh Kefale; Tegegne, Gobezie Temesgen (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug use evaluation is a performance improvement method that focuses on evaluation and improvement of drug use processes to advice optimal patient outcomes. Pneumocystis carinii pneumonia (PCP) is the most common acquired immune deficiency syndrome (AIDS) defining illness. Antibiotics being the most commonly prescribed group of drugs the problem of its overuse are a global phenomenon. Cotrimoxazole (CTX) preventive therapy (CPT) was shown effectively prevents PCP in patients with clinical evidence of immune suppression. CTX has been widely used as a treatment for common infections in many resource limited areas and as a result, CTX resistance among these pathogens has increased dramatically. In response to these problems, this study aims to evaluate the use CTX prophylaxis for opportunistic infections in human immunodeficiency virus (HIV) patients at Jimma University Specialized Hospital (JUSH). Methods: The study was done with retrospective cross-sectional review of medical records of HIV patients who have been on CTX prophylaxis in the hospital during September 11, 2012-September 10, 2013. To maintain the validity of data, the whole 135 patient cards were included in the study within the specified period. Data were collected from January 16, 2013 to February 15, 2013 using structured data collection format. Results: From the study subjects, 82 (60.74%) were females 85.93% of patients were used appropriate dose of CPT and 13.3% patients use CTX against contraindication. Regarding to adverse drug reactions (ADRs), 3.7% of patients were developed rash while 2.2% cases were developed nausea during the follow-up period of CPT. However, only 5.9% patients have documented information about ADR of CPT. On the top of this, CD4 count and hemoglobin test were done for 82.96%, 64.4% patients respectively during initiation of CPT. However, renal function tests were performed only for 2.96% of patients while initiating CPT. Conclusion: The use of CPT for people living with HIV/AIDS was found to be good in JUSH with regard to initiation and dosage. However, the practice of discontinuation of CTX, documentation of ADRs and follow-up for adverse effects of CTX should be improved by proper implementation and adhering to the national guideline of CPT.